Relación entre la formalidad y el acceso al crédito del microempresario, en la región Loreto periodo 2018-2022 - Saenz Amasifuen, Marcos (2024)
Access to credit is essential to carry out investment projects, since it provides the necessary financing for the acquisition of technological machinery and personnel to increase production. In this sense, this research focuses on providing a detailed analysis of the formality and access to credit of the microentrepreneur in Loreto-2018-2022. The research was developed through a quantitative-correlational type and non-experimental design that included 46,578 microentrepreneurs as a study population. The investigation determined that informality in Loreto went from 81.37% in 2018 to 85.02% in 2022, likewise the formal microentrepreneur sector in Loreto went from 35.18% in 2018 to 33.13% in 2022 and access to credit microentrepreneur went from 12.03% in 2018 to 19.78% in 2022. Likewise, Spearman's Rho Correlation Coefficient between equal to Rho=0.1960 and Sig. (bilateral)=0.000 being less than 5%, being significant, in this sense It is concluded that there is a weak positive correlation between formality and access to credit for microentrepreneurs in the Loreto region, period 2018-2022.